(untitled) (Advances in Systems Science and Applications, 2025)
Because the importance of the power circuit breaker for the liable operation of a power system added to the increasing demand for continuity in power delivery, non-invasive techniques for evaluating its condition have presented a significant evolution over the last five years. Today, the most promising technique is based on a radiometric system, which is based on analyzing the timing of the pole operation through the waveform of the transient signals radiated from the circuit breaker chambers, captured by sensors, and conveyed to a registering & processing unit. Even though this may seem to be a simple task it is rather far from being so as it is described and discussed in this work. Based on the experience of the authors, represented by several published papers about radiometry applied to power circuit breaker analyses, efforts towards the development of new equipment for replacing the commercially available digital oscilloscope became the milestone in the way to reaching a fully confident radiometric system. Although still much has to be done for this, important practical data are given over this work besides an approximate analytical approach for better comprehending the radiometry itself. The key issue is properly guaranteeing the registering of transient signals from the power circuit chambers when any switching is made, which has been shown as being a very challenging task. This work is intended to serve as a basic reference for every radiometric system applied to circuit breakers that may be in development.